Biophysical and biochemical characterization of a VHH-based IgG-like bi- and trispecific antibody platform. Issue 1 (1st January 2020) - Pekar, Lukas; Busch, Michael; Valldorf, Bernhard; Hinz, Steffen C.; Toleikis, Lars; Krah, Simon; Zielonka, Stefan
ABSTRACT: Here, we report the characterization of a VHH-derived IgG-like bi- and trispecific antibody platform that essentially relies on the replacement of the VH and VL regions of a conventional antibody by two independently functioning VHH domains. Consequently, a VHH is engrafted onto constant region CH1 while the other VHH-based paratope is engrafted on the constant region of the light chain, Cκ or Cλ, resulting in a tetravalent bispecific IgG-like molecule. Combined with a heavy chain heterodimerization technique, this platform allows facile engineering of bi- and trispecific antibodies with flexible valencies. We demonstrate the general applicability of this generic platform approach and elaborate on the limitations of specific formats.